ESENSI SANGHA SEBAGAI WADAH PEMBINAAN UMAT BUDDHA - anwar aman (Jurnal Pelita Dharma, 2016)
Perception on members of the Sangha or monks, particularly monks of Sangha Theravada Indonesia is very various. A few Buddhists and other religious community have a perception that Sangha today does not correspond to the truth of Buddha' teachings. There are some who argue that the monks of Sangha Theravada Indonesia are selfish, away from society, not concerned with the problems of the people around them. The monks of the Theravada tradition prefer to implement ‘silent' meditation at the monastery or the forest. However, some Buddhist laymen or even religious leaders including Buddhist monks argue that perception is not true. It does not match to reality of Sangha daily-life based on monks point of view. For some people, including researcher interested in observing and analyzing perceptions or assumptions developed in the community. To study this, the researcher used qualitative research method. The results of the research carried out showed that the essence of Sangha is the realization of Tiratana, alike the lush fields where farmers grow and harvest produce good results. From the aspect of worship, Sangha is a place for monks to develop themselves and to serve Buddhist Community. Sangha is a medium for monks as individual, in order to provide guidance and service Buddhist Community to conduct good deed as the teachings of Buddha.